Studies on the Role of Nerve Growth Factor in the Growth of Nerve Fibres from Sympathetic Ganglia - Recklies, Dorothea Anneliese (My University, 1976)
The role of nerve growth factor (NGF) in stimulation nerve fibre growth from sympathetic nervous tissue of the chick embryo was investigated both in vitro and in vivo. A method for the in vitro culture of sympathetic ganglia, using plastic tissue culture plates and a liquid medium, was developed which was convenient for the growth of large numbers of ganglia. The response to NGF in this system differs from that observed in the commonly used plasma-clot system in the time required for nerve fibre growth, the morphology of the nerve fibres and the effects of RNA synthesis inhibitors.
The capacity of several compounds other than NGF to stimulate nerve fibre growth was investigated. Both cAMP and, its butyrylated derivatives as well as E-type prostaglandins stimulated neurite extension. Similar results were obtained with sodium butyrate and other short chain fatty acids. Theophylline and papaverine, used as cyclic nucleotide phosphodiestrase inhibitors, inhibited neurite extension in the presence of NGF. Since none of the compounds tested stimulated neurite extension to the same extent as NGF it is suggested that they mimic some but not all the effects of NGF on sympathetic neurons. The stimulation of neurite extension from mature neurons may be distinct from the effects of NGF on the maturation and differentiation of neuroblasts.
The role of NGF during the development of sympathetic innervation in the chick embryo was investigated by measuring NGF levels in several organs (heart, duodenum, spleen, iris) at various stages of the incubation period and relating them to the establishment of sympathetic innervation in these tissues. NGF activity in tissue extracts was determined by bioassay. The activity of the enzyme dopamine-β-hydroxylase (DBH) was determined in the organs as an indication of the presence of sympathetic nerve terminals.
NGF levels in the tissues increased several-fold during embryonic development. This was not observed in tissues which are only sparsely or not at all supplied with sympathetic nerves (liver, leg muscle). DBH activity could only be detected in the organs during the last quarter of the incubation period. At this time NGF levels had already reached a maximum. No quantitative relationship between NGF levels and DBH activity was observed in any of the organs.
These data together with some histofluorescence studies on innervation patterns in the heart and duodenum of the chick embryo (Enemar et al., 1965) suggest a relationship between the NGF content of the target tissue and the establishment of sympathetic innervation. NGF levels in the target tissue may serve to regulate the onset and extent of ramification of sympathetic innervation during embryonic development.
Keywords: Biochemistry; Biochemistry